Wild Pedagogies Touchstones for Re-Negotiating Education and the Environment in the Anthropocene (Palgrave Studies in Educational Futures, 2018)
'This book leads an attack on the domestication of learning, the creeping formality, the structures and control, the standardizing, the separation of each of us from ourselves and our physical reality. This is a portrait of the physicality of children and the need to embrace this in education; the need to see education as humans in the world; the need to experiment with ideas and words that give meaning to our intuitions. An important argument. An important book.' -John Ralston Saul, essayist and novelist This book explores why the concept of wild pedagogy is an essential aspect of education in these times; a re-negotiated education that acknowledges the necessity of listening to voices in a more than human world, and (re)learning how to dwell in a place. As the geological epoch inexorably shifts to the Anthropocene, the authors argue that learning to live in and engage with the world is increasingly crucial in such times of uncertainty. The editors and contributors examine what wild pedagogy can truly become, and how it can be relevant across disciplinary boundaries: offering six touchstones as working tools to help educators forge an onward path. This collaborative work will be of interest to students and scholars of wild pedagogies, alternative education and the Anthropocene, and for all those engaged in re-wilding education. Bob Jickling is Professor Emeritus at Lakehead University, Canada. Sean Blenkinsop is Professor at Simon Fraser University, Canada. Nora Timmerman is Lecturer at Northern Arizona University, USA. Michael De Danann Sitka-Sage (formerly Michael W. Derby) is Researcher at Simon Fraser University, Canada. .